Liquid biopsy for detecting epidermal growth factor receptor mutation among patients with non-small cell lung cancer treated with afatinib: a multicenter prospective study - Fujii, Hiroaki; Nagakura, Hideyuki; Kobayashi, Nobuaki; Kubo, Sousuke; Tanaka, Katsushi; Watanabe, Keisuke; Horita, Nobuyuki; Hara, Yu; Nishikawa, Masanori; Miura, Kenji; Koizumi, Harumi; Ito, Yu; et al. (BMC cancer, 2022)
Background This study aimed to determine the effectiveness of liquid biopsy in detecting epidermal growth factor receptor (EGFR) mutations at diagnosis, disease progression, and intermediate stages. Methods This prospective, multicenter, observational study included 30 patients with non-small cell lung cancer treated with afatinib, harboring a major EGFR mutation confirmed by tumor tissue biopsy. We collected blood samples for liquid biopsy at diagnosis, intermediate stage, and progressive disease. Tissue and liquid biopsies were examined using Cobas [R] EGFR Mutation Test v2. Results Liquid biopsy detected EGFR mutations in 63.6% of the patients at diagnosis. The presence of metastasis in the extrathoracic, brain, and adrenal glands correlated positively with the detection of EGFR mutations. Patients with positive EGFR mutations at diagnosis had significantly shorter overall and progression-free survival than patients with negative EGFR mutations. Four of the 18 patients (22.2%) who reached progressive disease had positive EGFR T790M mutations. Three of 10 patients (30.0%) with progressive disease were positive and negative for T790M using tumor re-biopsy and liquid biopsy, respectively. The results of EGFR mutation by tissue re-biopsy were the same as those of liquid biopsy in the three patients who were positive for significant EGFR mutations but negative for the T790M mutation using liquid biopsy at progressing disease. Only two patients were positive for major EGFR mutations at intermediate levels. Conclusions Liquid biopsy can be a prognostic factor in EGFR-tyrosine kinase inhibitor treatments at diagnosis. Tumor re-biopsy can be omitted in patients with positive EGFR mutations by liquid biopsy at PD. Keywords: Cell-free deoxyribonucleic acid, Epidermal growth factor receptor, Liquid biopsy, Non-small cell lung cancer, Second-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors